Gender differences in caregiver–child relationship mediation of the association between violence exposure severity and adolescent behavior problems. (December 2015) - Yoon, Susan; Kobulsky, Julia M.; Voith, Laura A.; Steigerwald, Stacey; Holmes, Megan R.
Abstract: The main objectives of this study were to investigate (1) the relationship between mild, moderate, and severe violence exposure in the home and behavior problems in adolescents; (2) the caregiver–child relationship as a potential mediator in this relationship; and (3) gender differences. A series of path analyses were conducted using a sample drawn from the National Survey of Child and Adolescent Well-Being (NCSAW-I) of 848 adolescents (ages 11–15) who had been reported to Child Protective Services for maltreatment and who remained in their homes. Exposure to violence and the caregiver–child relationship were reported by adolescents. Both caregiver ratings and adolescent self-reports were used to assess adolescents' behavior problems. Path analysis indicated that exposure to mild and severe violence was directly associated with higher levels of child-reported behavior problems. However, exposure to violence was not directly associated with caregiver ratings of adolescent behavior problems. The caregiver–child relationship mediated the relationship between mild and moderate violence on both caregiver and child-reported adolescent behavior problems. Gender differences also emerged; for girls, the caregiver–child relationship mediated the effects of mild and moderate violence, whereas for boys, it mediated the effects of severe violence on behavior problems. Study findings suggest caregiver–child relationships as a critical underlying mechanism in the association between violence exposure and adolescent behavior problems, highlighting the importance of adding the caregiver–child relationship factor to intervention efforts.